2016
DOI: 10.1093/mnras/stw3152
|View full text |Cite
|
Sign up to set email alerts
|

Herschel/SPIRE observations of water production rates and ortho-to-para ratios in comets

Abstract: This paper presents Herschel/SPIRE spectroscopic observations of several fundamental rotational ortho-and para-water transitions seen in three Jupiter-family comets and one Oort-cloud comet. Radiative transfer models that include excitation by collisions with neutrals and electrons, and by solar infrared radiation were used to produce synthetic emission line profiles originating in the cometary coma. Ortho-to-para ratios (OPRs) were determined and used to derived water production rates for all comets. Comparis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Separately, the constant torque imposed by Mashchenko (2019) necessarily induces a spin-up in 'Oumuamua's rotation. While this is in agreement with the known spin-up effect of outgassing (Jewitt et al 2003;Drahus et al 2011;Gicquel et al 2012;Maquet et al 2012;Fernández et al 2013;Eisner et al 2017;Wilson et al 2017;Roth et al 2018;Kokotanekova et al 2018;Biver et al 2019;Combi et al 2020;Jewitt 2021Jewitt , 2022, the model used would lead to 'Oumuamua's destruction due to centrifugal forces. For example, Jewitt & Luu (2019a, 2019b predicted that the second interstellar object 2I/Borisov would suffer disintegration events due to the spin-up timescale implied by the nucleus size and production rates, which were later observed Jewitt et al (2020).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Separately, the constant torque imposed by Mashchenko (2019) necessarily induces a spin-up in 'Oumuamua's rotation. While this is in agreement with the known spin-up effect of outgassing (Jewitt et al 2003;Drahus et al 2011;Gicquel et al 2012;Maquet et al 2012;Fernández et al 2013;Eisner et al 2017;Wilson et al 2017;Roth et al 2018;Kokotanekova et al 2018;Biver et al 2019;Combi et al 2020;Jewitt 2021Jewitt , 2022, the model used would lead to 'Oumuamua's destruction due to centrifugal forces. For example, Jewitt & Luu (2019a, 2019b predicted that the second interstellar object 2I/Borisov would suffer disintegration events due to the spin-up timescale implied by the nucleus size and production rates, which were later observed Jewitt et al (2020).…”
supporting
confidence: 80%
“…While the outgassing behavior of 'Oumuamua is unknown, the substellar model is similar to the outgassing of at least one comet for which in situ measurements exist (Taylor et al 2017). Despite the relevance of the Sun-tracking jet to 67P, empirical results for larger samples of comets have demonstrated that outgassing torques are generally responsible for nucleus spin-up (Jewitt et al 2003;Drahus et al 2011;Gicquel et al 2012;Maquet et al 2012;Fernández et al 2013;Eisner et al 2017;Wilson et al 2017;Kokotanekova et al 2018;Roth et al 2018;Biver et al 2019;Combi et al 2020;Jewitt 2021Jewitt , 2022 or spin-down (Eisner et al 2017;Bodewits et al 2018;Farnham et al 2021).…”
Section: Discussionmentioning
confidence: 94%